BOOSTING STUDENTS’ PRONUNCIATION THROUGH SONG DICTATION - Ikhsan, Muhammad Khairi (Jurnal Curricula, 2017)
Most of EFL students argue that pronunciation is one of English components that is quite difficult to be mastered. It is proven by most students of English that the writer taught at College of Teacher Training and education (STKIP) PGRI West Sumatera. They get some difficulties in pronouncing particular words like the sounds of vowels, consonants, and diphthongs. It happened because most of sounds in English are not found in Indonesian contexts. To overcome this problem, the writer promotes an alternative way so that the students’ pronunciation can be better and improved. The way that the writer means  is using song dictation.